Tax stimulation of innovative activity in the Republic of Kazakhstan: current practice and problems of perfection (Journal of Economic Research & Business Administration, 2017)
Tax regulation is a measure of the indirect impact on elements such aseconomy, social and political processes which is made by the introductionor abolition of taxes, tax rates change, the establishment of tax incentivesand other measures of indirect impact. It is important for the economy ofKazakhstan to develop innovation as scientific and technological progressis one of the main factors of economic growth, therefore, special attentionshould be given for its state support. Successful development of innovationsin Kazakhstan can be supported by the optimizing tax stimulants which canbe represented by the tax benefits, the creation of economic zones and decreasingthe tax burden for persons engaged in innovative activities.In this article the author conducted a study using tax stimulants ininnovation. The author has analyzed the tax rules governing innovationactivities. The development state and the state involvement in innovation,recommendations to improve the tax stimulants are also studied in innovationactivities.